Kapasitas Pemerintah Desa dan Tantangan Peningkatan PADes: Studi Pengelolaan Sumber Daya Lokal di Desa Bagan Melibur - Yani, Destri; Alkadafi, Muammar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Merbau District in the Meranti Islands Regency has potential in agriculture, fisheries, oil, and tourism, with sago as its main commodity. Village funds support its utilization, but the Village Original Revenue (PADes) has not yet been established, and additional income is generated only by a few villages through cooperation with PT RAPP, with Bagan Melibur Village able to maintain it. Only three villages have active Village-Owned Enterprises (BUMDes), while six others have not optimally managed their regional potential. This study aims to examine the capacity of the Bagan Melibur Village government in generating PADes through local resources, as well as the supporting and inhibiting factors in producing PADes. The author used a qualitative approach to gain an in-depth understanding of Bagan Melibur Village through interviews, observations, and documentation. The research was conducted in the village due to its accessible location, involving 10 competent informants. Data were analyzed through four stages: collection, reduction, presentation, and conclusion. The results indicate that the Bagan Melibur Village government’s capacity to increase PADes is fairly good, supported by clear regulations, an organized structure, and competent personnel capable of managing village resources and finances transparently and accountably through participatory planning and digital administration, although challenges remain such as low community participation, limited entrepreneurial skills, rising raw material costs, and market access and geographic constraints